When timing matters—misdesigned dam filling impacts hydropower sustainability - Marta Zaniolo (Nature Portfolio, 2021)
Filling of dams, when coinciding with droughts, can lead to severe downstream hydrology and ecology problems. The authors hence here provide a multisectoral perspective, using a dam in Ethiopia as an example, to develop adaptive filling solutions that support decision making, favourable filling timing and an effective filling policy.